Synthesis of block copolymers using end-functionalized polyacetylenes as macroinitiators. Issue 28 (31st May 2018) - Shiotsuki, Masashi; Takahashi, Kei; Rodriguez Castanon, Jesus; Sanda, Fumio
Abstract : A block copolymer consisting of helically twisted polyacetylene and α-helical peptide was successfully synthesized for the first time. Abstract : Polyacetylenes substituted with phenyl, N-tert -butoxycarbonyl-l -valine 4-anilide, and ( S )-1-(acetoxy)ethyl groups with number-average molecular weights ranging from 3800 to 13 500 were synthesized by the polymerization of the corresponding acetylene monomers using [1, 1′-bis(diphenylphosphino)ferrocenePdBr(C6 H4 - o -CH2 OH)] as a catalyst.l -Lactide and γ-benzyl-l -glutamate N -carboxyanhydride were polymerized using the polyacetylenes as macroinitiators to obtain the block copolymers, some of which formed chiral secondary structures. A block copolymer consisting of helically twisted polyacetylene and α-helical peptide was successfully synthesized for the first time.